De Improperia en het jodendom - Poorthuis, Marcel (Jaarboek voor liturgieonderzoek, 1989)
The Improperia of Good Friday pose a considerable problem for scholarly research and for jewish-christian relations. On the one hand scholars emphasize the biblical and jewish roots of the Improperia, on the other hand they point to the relation between the Improperia and the long christian tradition of anti-judaïsm especially the accusation against the jews of deicide. In this article it is demonstrated that a merely historical or thematical approach to the Improperia and their sources is not sufficient to solve this vexing problem. Systematic comparison of related jewish and christian texts brings to light that prophetic criticism in jewish texts can be transformed by christians into an outright condemnation of judaïsm. This can be achieved with only very minor changes in the text (e.g. Melito and Byzantine hymns). Blaming of the whole jewish people in past and present for the passion and death of Christ turns out to be a perversion of jewish prophetic categorial criticism and of liturgical identification of past and present. This is rightly rejected by "Nostra Aetate". Neither historical roots in jewish texts nor similarity of themes are a warrant against anti-judaïsm in christian texts. Crucial is the division of roles. Many predecessors of the Improperia like the Byzantine hymns are anti-jewish because their criticism is directed towards the other, towards "a people that is no longer God’s people", the jewish people. These predecessors are today no longer acceptable for liturgical use. The Improperia of Good Friday themselves however are not anti-jewish because their prophetic criticism is directed not towards the other but towards "God’s people", the church.